DEVELOPMENT OF GOOGLE SITES MEDIA TO IMPROVE STUDENTS' LEARNING INTEREST IN THE IMPORTANCE OF HAVING SYAJA'AH CHARACTERISTICS AT MAN PEMATANG SIANTAR - Sirait, Azyana Alda; Nasution, Indah Widya Jaya Putri; Siregar, Muhammad Irfansyah; Halimaini K, Putri; Ilfah, Ade; Nasution, Wahyuddin Nur (Universitas Al-Amien Prenduan, 2025)
This research aims to develop learning media based on Google Sites to increase students' interest in learning, especially in the material